Establishment of a cell-based reporter assay for screening of hypoxia-inducible factor activities - Liew, Sien Yei (2013)
Hypoxia-inducible factor (HIF) is one of the most important transcription factors involves in cells survival under low oxygen concentrations, termed hypoxia. Hypoxia is associated with various human diseases from ischemic injuries to cancer. The central role of HIF in these conditions has made it as one of the main target molecules for drug discovery. Demand for HIF assay system is high. Cell-based HIF assay systems are preferred since they can provide direct data for intracellular biochemical changes. HIF assay systems which are currently available in the market offer limited sensitivity with restricted reproducibility at a high cost. Therefore, in the present study, a HIF assay was succesfully developed. The system used a Saos-2 human osteosarcoma cell line which is one of the most studied cell lines to express a luciferase protein in response to HIF activation. The luciferase gene construct which was previously cloned downstream of four copies of a hypoxia response element (HRE) of the erythropoietin (EPO) gene. EPO is one of the specific target genes of HIF. Therefore this assay can be used to measure HIF activation upon induction by candidate drugs of interest, by measuring the luciferase expression. This highly sensitive assay system offers a 40-times increased sensitivity compared to the currently available systems. This aspect would be highly beneficial to researchers since the increase in sensitivity can contribute towards result consistency and reproducibility leading to reduced wastage of precious drug candidates.